Iteration, Innovation und Dekorum in Opferlisten des Alten Reichs: Zur Vorgeschichte der Pyramidentexte - Morales, Antonio J. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2015)
The purpose of this paper is to illustrate early contexts for the rites conforming the offering Pyramid Texts of the Fifth and Sixth Dynasties. Although the original form of the recitations in the mortuary cult was oral, a process of entextualization came to fix these recitations in writing, first as aide-mémoire for ritualists and then as ‘actualisations monumentales’ for the deceased. A comprehensive analysis of the process of formation of the offering list from the Second Dynasty to the reign of Unas reveals a cogent association of the involved priestly services and items with the offering rites in the Pyramid Texts. In fact, it is suggested that the canonization of the offering list by the mid-late Fourth Dynasty resulted from an attempt to standardize the structure of offering services in Giza and Saqqara that later extended to the royal mortuary corpus.